The Effect of Human Milk on Modulating the Quality of Growth in Preterm Infants - Piemontese, Pasqua; Liotto, Nadia; Mallardi, Domenica; Roggero, Paola; Puricelli, Valeria; Giannì, Maria Lorella; Morniroli, Daniela; Tabasso, Chiara; Perrone, Michela; Menis, Camilla; Orsi, Anna; Amato, Orsola; et al. (Frontiers in Pediatrics, 2018)
Introduction: Human milk is the optimal nutrition for preterm infants. When the mother's own milk is unavailable, donor human milk is recommended as an alternative for preterm infants. The association among early nutrition, body composition and the future risk of disease has recently attracted much interest. The aim of this study was to investigate the effect of human milk on the body composition of preterm infants. Materials and Methods: Very low birth weight infants (VLBW: birth weight <1500 g) with a gestational age (GA) between 26 and 34 weeks were included. Clinical data, anthropometric measurements and nutritional intake in terms of the volume of human milk were extracted from computerized medical charts. The human milk intake was expressed as a percentage of target fortified donor human milk and/or target fortified fresh mother’s milk, compared with the total volume of milk intake during the hospital stay. All included infants underwent anthropometric measurements and body composition analysis (expressed as fat-free mass percentage) at term corrected age (CA) by air-displacement plethysmography. A comparison between infants fed human milk at <50% (group 1) and infants fed human milk at ≥50% of the total volume of milk intake (group 2) was conducted. Multiple linear regression analyses were conducted to explore the modulating effect of fortified human milk on fat-free mass at term CA. Results: Seventy-three VLBW infants were included in the study. The mean weight and GA at birth were 1248±198 g and 30.2±2.0 weeks, respectively. No differences were found regarding anthropometric measurements at birth, at discharge and at term CA between the two groups. The mean fortified human milk intake was 34.9±12.5 and 80.9±15.5% in groups 1 and 2, respectively (p<0.001). A multiple regression analysis corrected for sex and birth weight demonstrated that intake of ≥50% fortified human milk was associated with a higher fat-free mass percentage at term CA than intake of <50% fortified human milk. Conclusion: The use of target fortified human milk modulated growth and improved growth quality in vulnerable preterm infants. Thus, the use of donor human milk should be encouraged when fresh mother’s milk is insufficient or not available.